Woman with premature ovarian failure at age 15 becomes pregnant with ovodonation - Hilario, Roly (2015)
The case of an infertile 22 year-old woman with 3 years of cohabitation and history of menarche and premature ovarian failure (POF) at age 15 is presented. Secondary sex characteristics were normal, FSH was 69 mIU/mL, LH 21.5 mIU/mL, estradiol 5 pg/mL, normal thyroid profile, prolactin 0.22 ng/mL, glucose and insulin within normal limits; no alterations of the pituitary gland were detected by magnetic resonance. Karyotype was 46, XX. Transvaginal ultrasound showed a 46 x 20 x 25 mm hypothrophic uterus, endometrium 2.2 mm, hypotrophic ovaries. Administration of estradiol valerate/dienogest enlarged uterus to 69 x 22 x 33 mm (in one month) and 72 x 24 x 30 mm (in one year). Husband’s sperm count was 55.6 million/mL, progressive motility 24%, normal morphology 4%, and DNA fragmentation 14.2%. Autoimmunity and FMR-1 gene were not studied. Egg donation-ICSI-annexin column were performed obtaining 15 oocytes; fecundation occurred in in 12, and 4 embryos reached blastocyst stage, 2 embryos were transferred and 2 frozen. Single pregnancy was obtained with ongoing pregnancy. The frequency of premature ovarian failure cases at age 15 is estimated at 1/10 000 in women younger than 20 years, without apparent cause.